2022
DOI: 10.1088/1755-1315/969/1/012060
|View full text |Cite
|
Sign up to set email alerts
|

Microwave heating control system using genetic algorithm-based PID controller

Abstract: The superiorities of microwave heating technology have attracted many researchers for further development. Designing a satisfying temperature control system for the microwave system is one of them. To confirm that the controller can work with good system performance, the adjustment of controller parameters is important. Most previous research about microwave control systems did not focus on the tuning problem which is presented in this work. This paper provides the use of a genetic algorithm to adjust the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…More complete numerical results associated with Figure 4 can be shown in table 2. Since there is not any significant difference between MC-GA and MCIAE-GA, standard deviation that GA obtain after several running tests may become the next criteria to assess and highlight the repeatability of the algorithm [24]. As illustrated in table 3, the standard deviation of MC-GA is lower than that of MCIAE-GA after performing twenty running tests for each method.…”
Section: Figure 5 Objective Function Of Best Individual At Each Gener...mentioning
confidence: 99%
“…More complete numerical results associated with Figure 4 can be shown in table 2. Since there is not any significant difference between MC-GA and MCIAE-GA, standard deviation that GA obtain after several running tests may become the next criteria to assess and highlight the repeatability of the algorithm [24]. As illustrated in table 3, the standard deviation of MC-GA is lower than that of MCIAE-GA after performing twenty running tests for each method.…”
Section: Figure 5 Objective Function Of Best Individual At Each Gener...mentioning
confidence: 99%
“…Most previous techniques concentrate on the quality of the initial population seeding, such as random initialization, nearest neighbor, and K-means clustering [49][50][51]. Some researchers used GA to optimize PID, for instance, Guan and Jau [52], Swati K. et al [53], Tanvir ert et al [54], Gun B. S. [55], and Apriaskar et al [56]. On the other side, PSO is one of the EA's that was developed by James Kennedy and Russell Eberhart in 1995, for solving practical issues related to optimization, inspired by the behavior of living things.…”
Section: Introductionmentioning
confidence: 99%
“…By employing proficient controllers, the risks associated with heat non-uniformities can be mitigated [1]. It has been suggested that modeling plant dynamics is instrumental in designing controllers that yield satisfactory performance, as it elucidates the temperature profile of the heated product in relation to allocated microwave power, a valuable insight for control design simulations [7,8].…”
Section: Introductionmentioning
confidence: 99%